Characteristics of Urinary Tract Infection in 1-17 Years Old Children - Febriani, Tien Budi; Lestari, Rini Dwi; Nugraheti, Prita Murani (Universitas Aisyah Pringsewu, 2024)
Urinary tract infection is a disease that is common in children and is characterized by a significant number of bacteria in the urine. UTI incidence is still high, is the second leading cause of infectious disease morbidity in children after respiratory tract infection. In Indonesia, 200 children were evaluated by 35% in children 1-5 years old and 22% of children aged 6-10 years suffering from a urinary tract infection, or approximately 33% in men and 67% in women. This study aimed to find the characteristics of urinary tract infection in children aged 1-17 years in Wonosari hospital. This study shows the characteristics of urinary tract infection in children aged 1-17 years in Wonosari hospital, Yogyakarta. This study uses a cross-sectional study design obtained from the medical record in the period 2018 to 2019. In this study, 41 pediatric patients with urinary tract infections, 16 (39%) male, 25 (61%) female with an age range most 1-5 years old 20 (48,8%). A total of 41 patients with urinary tract infections, 17 patients (41,5%) with symptoms of nausea and vomiting, 31 (75,6%) with good nutrition. Urinalysis result with positive leucocyte esterase 32 (78%). And 20 patients (41,4%) with penicillin class of antibiotic therapy. Outcome healed 29 (70,7%). Urinary tract infections are the most at the age of 5-12 years. Clinical symptoms, especially naucea and vomiting. Urinalysis results do not exclude the diagnosis of urinary tract infection, so that the child vomits aged 1 to 17 years with no obvious cause of urinary tract infections should be considered.